Over 700 MHz –3 dB Bandwidth UOWC System Based on Blue HV-LED With T-Bridge Pre-Equalizer - Ziying Zhang; Yuanjia Lai; Junlong Lv; Pan Liu; Dongdong Teng; Gang Wang; Lilin Liu (IEEE Photonics Journal, 2019)
To achieve a good balance among the raw modulation bandwidth, the output optical power, and the dynamic swing range, three small GaN-based blue light-emitting diode (LED) cells are cascade interconnected on chip to form a 9 V HV-LED. A single-stage T-bridge equalizer is proposed to upgrade the –3 dB bandwidth and –6 dB bandwidth of a visible light communication/underwater optical wireless communication (VLC/UOWC) system based on the HV-LED to be over 700 and 900 MHz, respectively. To the best of our knowledge, it is the widest bandwidth of a VLC/UOWC system at the similar LED optical power level (120 mW). Under the forward error correction (FEC) limit of $3.8 × {10^{ - 3}}$ , data rates of 3.4 Gb/s over 1.8-m free-space transmission and 3 Gb/s over 1.2-m underwater channel are obtained using 16QAM-OFDM modulation scheme without complex algorithm. The T-bridge equalizer also improves the error free modulation bandwidths up to 450 MHz under 16QAM-OFDM, and up to 600 MHz under 8QAM-OFDM, respectively. Furthermore, the conjunction of the developed HV-LED and T-bridge equalizer endows the merit of a wide linear region of the modulation response, which will make the communication system be more tolerance to LED's degradation and system fluctuations.